1982
DOI: 10.1111/j.1755-618x.1982.tb00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Education and support for dominant ideology*

Abstract: Utilisant les résultats du sondage national sur la qualité de la vie de 1977, nous avons examiné les quatre hypothèses qui expliquent l'influence de l'instruction sur l'opinion publique au sujet de l'inégalitééconomique. Les hypothèses sont l'instruction, la socialisation, la reproduction, et l'investissement. L'élément français‐anglais et les différences d'âge sont examinés également. Les résultats des analyses multivariées favorisent la socialisation ainsi qu'une des versions de l'hypothèse d'investissement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
5

Year Published

1990
1990
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 10 publications
2
12
0
5
Order By: Relevance
“…Sociological research has shown the importance of the level of education as well as the field of study on determining people's value orientation. Especially in universities, students develop their own ideas (Baer and Lambert, 1982). It is also repeatedly shown that the field of study affects and shapes values, attitudes and behaviour (Crotty, 1967;Guimond et al, 1989;.…”
Section: Social Class and Educationmentioning
confidence: 98%
See 1 more Smart Citation
“…Sociological research has shown the importance of the level of education as well as the field of study on determining people's value orientation. Especially in universities, students develop their own ideas (Baer and Lambert, 1982). It is also repeatedly shown that the field of study affects and shapes values, attitudes and behaviour (Crotty, 1967;Guimond et al, 1989;.…”
Section: Social Class and Educationmentioning
confidence: 98%
“…However, some scholars have argued the education of individuals to be an important factor for shaping attitudes, political preferences and lifestyle forms (Baer and Lambert, 1982). Therefore, one can claim that differences in attitudes, behaviour and lifestyle forms between the members of the newly distinguished social classes are not related to social class positions but instead to educational differences.…”
Section: Introductionmentioning
confidence: 99%
“…In offering these conjectures, we are not taking any position regarding how education should be understood. There has been some discussion in the recent literature on class and politics about whether the observed correlations between education and political opinions are best understood in terms of socialization, enlightenment, or investment (Baer and Lambert, 1982;Curtis and Lambert, 1976;and Lambert and Curtis, 1979). There are real issues at stake in this controversy, but none that are directly relevant here.…”
Section: Here We Employ a Simple Manual-non-manual Occupational Classmentioning
confidence: 99%
“…Comme nous l'avons évoqué, Bourdieu et Passeron ont sur ce point des positions ambivalentes, l'essentiel étant pour eux que tout le monde y adhère. Les sociologues canadiens Baer et Lambert (1982), étudiant la perception des inégalités en général, présentent quatre hypothèses qu'il est possible d'adapter à la présente problématique. Se référant à Bourdieu et Passeron, ces chercheurs proposent tout d'abord l'hypothèse dite de la « reproduction » : le système scolaire fait intérioriser à tous, quel que soit le niveau d'instruction atteint, l'idée que les positions sociales héritées sont liées au mérite individuel.…”
unclassified
“…Enfin, Baer et Lambert (1982) envisagent une dernière hypothèse, dite de l'« investissement » : l'adhésion à l'idéologie dominante serait liée à la décep-tion ou à la satisfaction de l'individu quant à la correspondance entre son 235 niveau d'instruction et le niveau social atteint, ce qui rejoint les constats de Dubet évoqués précédemment. Au total, ces hypothèses, concernant certes la perception des inégalités de manière générale, laissent entendre que la question du rôle de l'école dans l'intériorisation de la méritocratie scolaire est plus complexe que ce que suggéraient Bourdieu et Passeron.…”
unclassified